Graphene and MXene-based transparent conductive electrodes and supercapacitors - Nicolosi, Valeria; Zhang, Chuanfang (John) (My University, 2019)
The great popularity of portable, smart electronics has intensively stimulated the development of energy storage devices and other cutting-edge products, such as displays and touch panels. Interactive devices such as smart phone, tablets, and other touchable devices require mechanical robust transparent conductive electrodes (TCEs). Developing transparent supercapacitor as the power source is of significance to the next generation transparent electronics. Recently, graphene and MXene, the two representatives in the large two-dimensional family, have shown excellent electronic conductivity and attracted great research attention in the energy storage field. Importantly, high-performance TCEs are the prerequisite of building transparent supercapacitors. This review provides a comprehensive analysis of graphene and MXene-based flexible TCEs covering detailed thin film fabrication methods, evaluation metrics, performance limitations as well as approaches to beat these limitations. We especially focus on the fundamentals in the TCEs, such as figure of merit, percolations as well as conductivity behaviours. Graphene and MXene-based transparent supercapacitors are analysed, with a particular focus on transparent, freestanding graphene papers. Finally, the challenges and prospects of MXene for TCEs and transparent supercapacitors, in conjunction with a critical analysis of MXene shortcomings, are discussed.
Keywords: Graphene; MXene; Transparent supercapacitor; Figure of merit; Transparent conductive electrodes (TCEs)